Comparison of Short-Sprint and Heavy Strength Training on Cycling Performance - Kristoffersen, Morten; Sandbakk, Øyvind; Rønnestad, Bent R.; Gundersen, Hilde (Frontiers in Physiology, 2019)
Purpose: To compare the effects of short-sprint training (SST) and heavy-strength training (HST) following a 4-week strength-training period on sprint and endurance capacities in well-trained cyclists. Methods: Twenty-eight competitive cyclists (age 29 ± 6 years) with maximal oxygen uptake (V ̇O2max) of 61.1 ± 5.9 mL·min-1·kg-1 participated. After a 4-weeks preparation strength-training period, the participants were randomized to add either HST or SST to their usual endurance training for the subsequent 6 weeks. Body composition, V ̇O2max and power output at blood lactate concentration ([La-]) of 4 mmol·L-1, as well as a 100 min cycling test including 6-sec and 30-sec sprints, 60 min cycling at [La-] of 2 mmol·L-1 and 5-min all-out cycling were performed before the 4-week preparation strength-training period, and before and after the 6-week intervention period. In addition, 1 repetition maximum (RM) in half-squat and 55-m maximal sprints on the cyclists’ own bikes were measured before and after the 6-week intervention. Results: SST was superior to HST in 6-sec sprint performance, both in a fresh state (4.7 ± 2.6% vs. 1.1 ± 3.5%) and after prolong cycling (6.1 ± 1.8% vs. 1.8 ± 4.2%), in 30-sec sprint (3.7 ± 2.8% vs. 1.3 ± 2.5%) and in 55-m seated sprint on own bike (4.3 ± 2.1% vs. 0.2 ± 1.8%) (all p < .002). HST induced a larger 1RM improvement in the half-squat test than SST (9.3 ± 3.6% vs. -3.9 ± 3.8%; p < .001). No group differences were revealed in the 5-min all-out test, V ̇O2max, power output at 4 mmol·L-1 [La-], or in gross efficiency. Conclusion: SST led to a greater increase in average and peak power output on all sprint tests compared to HST, whereas HST led to a greater increase in maximal strength. No group differences were found in relative changes in endurance capacities. Altogether, our results show a high degree of specificity in the adaptations of both SST and HST.